Malignant lymphoma in Eastern India: A retrospective analysis of 455 cases according to World Health Organization classification - Santosh Kumar Mondal; Palash Kumar Mandal; Tarun Kumar Samanta; Subrata Chakaborty; Saptarshi Dutta Roy; Shravasti Roy (Indian Journal of Medical and Paediatric Oncology)
Background: Malignant lymphoma (ML) is one of the most common cancers and is most prevalent in developed countries. The distribution of different subtypes of ML varies in the different geographical locations according to World Health Organization (WHO) Classification. Aims and Objectives : The study was aimed to analyze the different patterns of ML in Eastern India and to compare it with other geographical locations. Materials and Methods: Four hundred and fifty five patients of two large hospitals in Eastern India were included over a period of four years and were categorized according to WHO classification, using the morphology and immunohistochemistry. Results: There were 347 (76.3%) non Hodgkin lymphomas (NHL), and 108 (23.7%) Hodgkin lymphomas (HL). Diffuse large B-cell lymphoma was the most common of the NHL type (35.2%) followed by the follicular lymphoma (19.3%). B-cell lymphoblastic lymphoma was the least common type of NHL (1.4%). Mixed cellularity (33.3%) and nodular sclerosis (26.9%) were the two most common type of HL. Childhood lymphoma comprised of 12.5%of all ML. T-cell NHL and HL were the common lymphomas in this age group. Conclusion: Incidence of follicular lymphoma is lower compared to western studies and mixed cellularity is the most common subtype of HL unlike nodular sclerosis subtype in Western world. Burkitt′s type NHL though is the most common subtype of childhood ML in many studies. However, in our study, T-cell NHL is the most common type of childhood ML.